The Role of Shear-Wave Elastography of the Spleen in Ruling out the Presence of High-Risk Varices in Non-Alcoholic Fatty Liver Disease (NAFLD) - Vasile-Andrei Olteanu; Catalin-Victor Sfarti; Gheorghe G. Balan; Oana Timofte; Elena Gologan; Dana Elena Mitrică; Georgiana-Emmanuela Gilca-Blanariu; Cristina Gena Dascalu; Ion Sandu; Gabriela Ştefănescu (Applied Sciences, 2023)
The progression of liver fibrosis and the presence of portal hypertension are two key points in the follow-up and severity assessment of patients with chronic liver disease. Objective evaluation of such aspects has proven to be difficult due to the lack of reproducible and standardized non-invasive methods. Therefore, the aim of this study was to evaluate whether spleen stiffness (SS) can rule out the presence of high-risk varices (HRVs) in patients with non-alcoholic fatty liver disease (NAFLD). We designed a prospective follow-up of a cohort of 48 consecutive patients diagnosed with compensated advanced chronic liver disease (cACLD) due to NAFLD, between January 2020 and January 2021. After clinical evaluation, laboratory testing, ultrasonography (US), and shear-wave elastography (2D-SWE.GE) of both the liver and the spleen, patients were endoscopically screened for esophageal varices, gastric varices, and portal hypertensive gastropathy. Correlations and predictors were assessed. After univariate, multivariate, and predictive analyses, SS could be referred to as an independent predictor for high-risk varices (AUROC 0.987, p < 0.001, OR 4.985, 95% CI: 1.57–15.73, p = 0.006), with a calculated cutoff value of 17.95 kPa. These results are consistent with those of other, similar studies using both 2D-SWE.GE and a similar module (2D-SWE.SSI) in patients with metabolic liver disease. When confirmed by subsequent larger studies, SS could potentially become a useful non-invasive tool in the assessment of clinically significant portal hypertension in patients with advanced fatty liver disease.